Identification of a pleiotropic locus on chromosome 7q for a composite left ventricular wall thickness factor and body mass index: the HyperGEN Study - Hopkins Paul N; Rao Dabeeru C; Kitzman Dalane W; Oberman Albert; Li Na; Devereux Richard B; Tang Weihong; Claas Steven A; Arnett Donna K (BMC, 2009)
Abstract Background Left ventricular (LV) mass and wall thickness are closely associated with measures of body size and blood pressure and also correlated with systolic and diastolic function, suggesting a contribution of common physiologic mechanisms, including pleiotropic genes, to their covariation. Methods Doppler echocardiography was performed in 434 African-American (1344 individuals) and 284 white families (1119 individuals). We conducted a genome-wide linkage scan for LV mass, LV structure and function, and composite factors derived from a factor analysis of LV structure and function in the HyperGEN Study population. Results Factor analysis identified (i) a LV wall thickness factor correlated strongly with interventricular septal thickness (IVSTd) and posterior wall thickness (PWTd) and (ii) a LV diastolic filling factor strongly correlated with early and atrial phase peak transmitral filling velocities. The LV phenotypes and composite factor scores were analyzed in multipoint variance components linkage model implemented in SOLAR with 387 microsatellite markers. In whites, the two highest LODs were 3.42 for LV atrial phase peak filling velocity at 144 cM on chromosome 1 and 3.12 for the LV wall thickness factor at 160 cM on chromosome 7. The peak LODs of the component traits (IVSTd and PWTd) clustered at the same region as the composite factor. Adjusting the factor score for body mass index (BMI) substantially reduced the peak LOD at this region (LOD = 1.92). Bivariate linkage analysis of the composite factor with BMI improved LOD to 3.42 at 158 cM. Also in whites, suggestive linkage was observed on chromosomes 2 and 4 for LV mass, chromosomes 3, 5, 10, and 17 for LV atrial phase peak filling velocity, and chromosome 10 for LV diastolic filling factor. In African Americans, suggestive linkage was observed on chromosome 12 for LV mass, chromosome 21 for IVSTd, and chromosome 3 for LV internal diameter at end-diastole. Conclusion Our study suggests that a region on chromosome 7 contains pleiotropic genes contributing to the variations of both LV wall thickness and BMI in whites.